Bureau Of Mines Research On Recycling Scrapped Automobiles - K. C. Dean (The National Institute for Occupational Safety and Health (NIOSH), 1985)
Discarded automobiles represent the greatest single resource of reusable metals, plastics, and rubber in the United States. This report presents results of Bureau of Mines research, conducted from 1965 to 1983, on separating and recovering useful materials from the scrapped hulks, using old and new metallurgical techniques combined with standard scrapyard methods. The Bureau determined the materials composition of three composite cars designated as circa 1960, mid-1970's, and early 1980's, and used these cars to study smokeless incineration and hand-sorting techniques. In studies on treating rejects from automobile shredders, the Bureau designed a process that included air classification, water elutriation, magnetic separation, handpicking, and heavy-medium separation, and also investigated cryogenics and liquation. Complete recovery of cop-per and other metals was economically made by hand and tool dismantling, leaching, or selective melting of starters and generators. Techniques are also discussed for plastic recovery and waste tire treatment.